A Career Life-Cycle Perspective on Women's Health and Safety: Insights From the Defense Health Board Report on Military Women's Health. Issue 4 (1st April 2022) - Kaplan, Robert S.; Chukwura, Chizoba L.; Gorman, Gregory H.; Lee, Vivian S.; Good, Chester B.; Martin, Kathleen L.; Ator, Gregory A.; Parkinson, Michael D.
Abstract : Women comprise an increasing percentage of U.S. military personnel. The Department of Defense (DoD) recognizes that women's health requires attention to workplace design, physical standards for entry, employment practices, equipment, and health monitoring. The DoD approach offers lessons for civilian employers in traditionally male-dominant fields. Abstract : Objective: Women's health has demanded more attention from employers as women integrated into the workforce. Traditionally male-dominant fields and occupations require special attention to workplace design, physical standards for entry, employment practices, equipment, and health monitoring. This editorial summarizes the Defense Health Board's (DHB) review of Active Duty Women's Health and its recommendations grounded in a woman's career life-cycle. Methods: The DHB reviewed the Department of Defense and foreign militaries' current women's health services, relevant policies and practices, peer-reviewed scientific literature, and subject matter expert interviews. Results: The DHB's recommendations centered on a comprehensive approach to education, health care access and treatment, professional workforce development, workplace standards and equipment, and accountable outcomes metrics to guide improvement. Conclusions: Employers can learn how to reduce morbidity, leading to a healthier and more productive female workforce.